2012
DOI: 10.1002/mop.27275
|View full text |Cite
|
Sign up to set email alerts
|

Triple band‐notched UWB monopole antenna with two resonator structures

Abstract: We propose a novel configuration of a triple band‐notched ultra‐wideband (UWB) antenna. The designed structure is based on an elliptical monopole antenna combined with a complementary split ring resonator (CSRR) structure and a spiral resonator. The spiral resonator can achieve the dual‐band notched performance at WiMAX band and ITU 8 GHz by adjusting the length and width of a spiral line. Besides, the CSRR can obtain the notched band at WLAN 5 GHz by changing the radius of a ring slot. The designed antenna sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The split ring resonator is self‐resonant and has a resonant frequency that is determined mainly by its loop inductance and the capacitances resulting from the cuts, which open the loop. The salient feature for the metamaterials is that the electrical size of a single unit cell is small compared to the wavelength; hence it can be effectively used for creating narrow band notches . The proposed structure is a single ring modified triangular split ring resonator with split at the end and a conductor extension inside the triangle as shown in Figure .…”
Section: Proposed Antenna Designmentioning
confidence: 99%
“…The split ring resonator is self‐resonant and has a resonant frequency that is determined mainly by its loop inductance and the capacitances resulting from the cuts, which open the loop. The salient feature for the metamaterials is that the electrical size of a single unit cell is small compared to the wavelength; hence it can be effectively used for creating narrow band notches . The proposed structure is a single ring modified triangular split ring resonator with split at the end and a conductor extension inside the triangle as shown in Figure .…”
Section: Proposed Antenna Designmentioning
confidence: 99%
“…Band notched monopole antenna and hybrid antenna have also been investigated for making antenna suitable for multiband applications. [7,8] Bemani et al [9] reported triple band antenna structure by the use of multisegment rectangular DRA (RDRA). But the main problem *Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…The third switch is embedded among the square ring shaped-slot to filter the X-band. In comparison with the presented antennas in [3][4][5][6][7][8][9][10][11][12][13][14], the proposed antenna is compact and uses varied and simple methods to generate single or double notch bands.…”
Section: Introductionmentioning
confidence: 99%